THE INFLUENCE OF EYESTALK ABLATION ON THE REGULATION OF HAEMOLYMPH SODIUM CONCENTRATION IN THE PRAWN PENAEUS INDICUS H. MILNE EDWARDS - Kiron, V; Diwan, A D (Indian Journal of Fisheries, 2011)
Removal of the eyestalks of the prawn Penaeiis indiciis resulted in an increase in the haemolymph-sodium level. This increase was more evident in bilaterally ablated animals. Injection of eyestalk extract into destalked animals helped them to restore the level almost similar to that of normal animals